The Economic Development of Creative Community Based on Cultural Capital in the Northern Economic Network - Phusit, Rattigan (College of Asian Scholar Journal, 2024)
This study aimed (1) to study factors driving the economy affecting activities in the creative community process based on cultural capital in the northern economic network, (2) to study activities in the creative community economic process based on the cultural capital affecting allocation of excess profit of the communities in the northern economic network, (3) to study factors driving the economy affecting the allocation of excess profit of the communities in the northern economic network, and (4) to set guidelines for economic development of the creative communities based on the cultural capital in the northern economic network. The quantitative were conducted in 5 provinces; Chiang Rai, Nan, Lampang, Phitsanulok, and Nakhon Sawan. The sample group consisted of 500 people, 100 people per province, and a simple random sampling method was used, by using a questionnaire as a tool to collect data from the sample group. The statistics utilizing in the research were Pearson Product Moment Correlation Coefficient. The results of the research showed that (1) the factors driving the community economy were human resource development, group or community development, and physical infrastructure development. They had a positive effect on activities in the community economic process at a statistically significant level of 0.01. The factors that drive the community economy in the field of development of community economic fundamentals had a statistically significant negative effect on the activities in the community economic process at the 0.01 level. (2) Activities of the community economic process such as production, consumption, and processing had positive effect on the allocation of excess profit, statistically significant at 0.01 level, and the activities of the community economic process in the field of marketing resulted negative to the allocation of excess profit of the communities, statistically significant at 0.01 level. (3) Factors driving the community economy in the field of human resource development, group or community development, and the development of the community's physical infrastructure had positive effect on the allocation of community’s excess profit, statistically significant at 0.01 level, and factors driving the community economy in terms of economic fundamental development of the community resulted negative to the allocation of excess profit of the communities, statistically significant at 0.01 level. (4) Guidelines for creative community’s economic development based on the cultural capital in the northern economic network should use community’s areas as a setting for managing community’s economic factors by linking with the activities of community economic process and for the allocation of community’s excess profit as a mechanism for managing processes. The activities of the community economic process should develop by creating a body of knowledge of the communities to create innovations in the community economic development and elevate the existing community to be strong in connection with the allocation of excess profits of the community. There is a strategic plan for community economic development for systematic management and linking the community strategic plan with relevant agencies to lead to sustainable development of the creative community economy based on the cultural capital.